Evaluation of mean shelling efficiency of Bambara nut at different speed levels and moisture contents using shelling machine - Kogh, Donatus Asua; Irtwange, Simon V; Anaka, Bill; Gaydaybu, James Flomo; Tiough, Momngu (Journal of Postharvest Technology, 2021)
Studies have shown that Bambara nut has not received maximum attention in area of research as it is the third most important grain after ground nut and cowpea. Cracking this nut requires a cracker since the manual means requires a lot of human efforts but the cracker works better and more effective when the shelling efficiency are achieved at different moisture content. This study therefore was on evaluation of mean shelling efficiency of Bambara nut at different speed levels and moisture content using a modern Sheller. Between group design was used as a design for this study and the data was collected at different stages that is categories of shelling efficiency which are completely shelled, partially shelled, completely shelled and broken and not shelled with the respective weight of bambara nut loaded on the machine, the weight of seeds obtained after shelling. One way analysis of variance was used to test the significant difference and the result indicated that there was a significant difference in the performance of the machine based on the shelling efficiency. Findings further shows the independent effect of speed, moisture content and shelling efficiency on the performance of the machine. On the interaction effect, speed*moisture content, speed*shelling efficiency, moisture content*shelling efficiency and speed*moisture content*shelling efficiency were also considered. The finding showed that the speed level of 275 RPM with the 7% moisture content has the highest level of shelling efficiency with the mean of 97.8 (SD = 6.85) while the least shelling efficiency is found when you have 300 RPM with 9% moisture content with an average completely shelled 4.10 (SD = .78). It was recommended among others that in using this modern cracker, Bambara nut should be shelled at 7% moisture content and at the speed of 275 RMP.